Organo‐montmorillonite modified wood flour/poly (lactic acid) composites via different modification process. Issue 2 (24th November 2020) - Wang, Zhiping; Wang, Chen; Qin, Ye; Huang, Anmin; Liu, Ru
Abstract: In this paper, four varieties of wood flour (WF)/poly (lactic acid) (PLA) composites by organo‐montmorillonite (OMMT) modification were fabricated via different modification process. The distribution of OMMT was characterized and the mechanical capacities of these composites were tested. After different OMMT‐modified process, the mechanical capacities of composites were distinctly different. However, except for the impact strength, almost the whole mechanical capacities showed improvements after modifying by OMMT; composite made of pure PLA and OMMT‐modified WF behaved the best mechanical properties, while composite made of pure WF and OMMT‐modified PLA behaved the worst; either for PLA modified by OMMT or WF/PLA composites modified by OMMT, the existence of the OMMT aggregates could cause damage to the mechanical properties. However, intercalated OMMT into WF or WF/PLA composite was beneficial to the mechanical properties. Abstract :